2011
DOI: 10.1080/02701367.2011.10599782
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Correlates for Children With Autism Spectrum Disorders in Middle School Physical Education

Abstract: This study examined potential correlates that might influence physical activity (PA) of adolescents with autism spectrum disorders (ASD) in physical education. Students with (n = 19) and without (n = 76) ASD wore an accelerometer during physical education. Data were collected in 38 physical education lessons. The results showed that (a) students with ASD were less physically active than their peers, (b) their PA was related positively to their social interaction with peers, and (c) their moderate to vigorous P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 25 publications
3
64
0
2
Order By: Relevance
“…12 Pan et al (2011) focused on activity levels during PE class and found that among children with ASD, PA during school PE was positively related to their interactions with their peers, and MVPA was associated with the physical environment (indoor, outdoor, or a combination) and instructor-related characteristics, such as gender and specialized training in physical education. 26 Based on parent interviews , LaVesser et al (2011) identified difficult behaviors among young children with ASD as a common reason for non-participation in this population rather than limited opportunity for PA. They speculated that child behavior problems may lead to increased parental stress, which in turn may affect child participation.…”
Section: Discussionmentioning
confidence: 99%
“…12 Pan et al (2011) focused on activity levels during PE class and found that among children with ASD, PA during school PE was positively related to their interactions with their peers, and MVPA was associated with the physical environment (indoor, outdoor, or a combination) and instructor-related characteristics, such as gender and specialized training in physical education. 26 Based on parent interviews , LaVesser et al (2011) identified difficult behaviors among young children with ASD as a common reason for non-participation in this population rather than limited opportunity for PA. They speculated that child behavior problems may lead to increased parental stress, which in turn may affect child participation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors speculated that questionnaires may not capture behaviors such as roaming and pacing that are frequently observed in children with ASD. Pan et al 117 , Macdonald et al 118 , and Memari et al 119 have reported declines in physical activity with age in cross-sectional analyses in children and adolescents with ASD. The relationship between weight status and physical activity were not reported in these studies.…”
Section: Other Potential Risk Factors For Obesity In Children With Asdmentioning
confidence: 99%
“…Physical activity has been suggested to help children with ASD reduce maladaptive behaviors and improve their overall health (Bandini et al 2013;Janssen and Leblanc 2010;Magnusson et al 2012;Pan and Frey 2006;Pan et al 2011aPan et al , 2011c. Participation in physical activity is often a challenge for children with ASD because of their poor motor functioning and low self-esteem.…”
Section: Part Iii: Physical Activity Assessment For Children With Asdmentioning
confidence: 98%